Sistem Pemantauan Ruangan Dengan Server Raspberry Pi - Egrit Nurcahyo Wijatsongko; Agfianto Eko Putra; Bambang Nurcahyo Prastowo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2015)
Continuous record will overload storage, due to big size recorded video files. One of the solution to this problem is to make system only record at necessary time. The example of the “necessary time” is when someone enter the room. Because of that, surveillance system which can detect motion in the room is needed. In this research, mentioned problem was tried to be solved by design and build a mini computer (Raspberry Pi) based room surveillance system. This surveillance system is made with Motion program. Motion program handle motion detection and streaming. Besides that, system also made so it can send notification via email, when motion is detected. For security and back up data reasons, system will also upload recorded video to Google Drive. System consists of one server and one client that are connected using WLAN network. The System performance was tested by observing recorded video frame rates as parameter. The motion detection of the system was also tested on various light intensity. From the test, got that the best condition for the system is at frame size 320x240 with light intensity more than 8 lux.